Enhancing students’ vocabulary knowledge using the Facebook environment - Kabilan, Muhammad Kamarul; Zahar, Tuti Zalina Mohamed Ernes (Indonesian Journal of Applied Linguistics, 2016)
This study investigates the effectiveness of using Facebook in enhancing vocabulary knowledge among Community College students. Thirty-three (33) Community College students are exposed to the use of Facebook as an environment of learning and enhancing their English vocabulary. They are given a pre-test and a post-test and the findings indicate that students perform significantly better in the post-test compared to the pre-test. It appears that Facebook could be considered as a supplementary learning environment or learning platform or a learning tool; with meaningful and engaging activities that require students to collaborate, network and functions as a community of practice, particularly for introverted students with low proficiency levels and have low self-esteem.